Existence and Uniqueness Theorem of Fuzzy Stochastic Ordinary Differential Equations - Kareem, Nabaa R.; Fadhel, Fadhel S.; Al-Nassir, Sadiq (Iraqi Journal of Science, 2023)
A fuzzy valued diffusion term, which in a fuzzy stochastic differential equation refers to one-dimensional Brownian motion, is defined by the meaning of the stochastic integral of a fuzzy process. In this paper, the existence and uniqueness theorem of fuzzy stochastic ordinary differential equations, based on the mean square convergence of the mathematical induction approximations to the associated stochastic integral equation, are stated and demonstrated.